Pengaruh Persepsi Masyarakat, Lokasi, dan Religiusitas terhadap Minat menjadi Nasabah di Bank Syariah (Studi Kasus Masyarakat Desa Moyoketen Kecamatan Boyolangu Kabupaten Tulungagung) - Andika, Irza; Khoiriawati, Novi (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2023)
This research is motivated by the rapid development of Islamic banking. Factors such as public perception, location, and religiosity are important to study, because Islamic banking institutions need to evaluate and develop in order to increase their existence by recruiting new customers and retaining existing customers. The purpose of this study was to determine and test the effect of community perception, location and religiosity on the interest of the people of Moyoketen Village, Boyolangu District, Tulungagung Regency to become customers in Islamic banks. The research approach used is quantitative with associative types. The population of this study was the community in Moyoketen Village aged 18-56 years as many as 1454 and the sample used was 94 respondents. The results of the study were processed using SPSS software version 25 which shows that people's perceptions are influential. The data used in this study are primary data obtained by using a questionnaire. The data analysis used in this research is validity test, reliability test, classic assumption test, multiple linear regression analysis, f test, t test, and the coefficient of determination with the help of SPSS version 25. The results of this study indicate that public perceptions have a direct effect on interest people become customers in Islamic banks with significance (0.00 <0.05), location has a direct effect on people's interest in becoming customers in Islamic banks with significance (0.00 <0.05), and religiosity has a direct effect on public interest being a customer in an Islamic bank with a significance (0.01 <0.05) and community perceptions, location, and religiosity simultaneously influence the public's interest in becoming a customer in an Islamic bank with a significance value (0.00 <0.05). Thus, it can be interpreted that the influence of public perception, location, and religiosity on the intention to become a customer at an Islamic bank is 65.4% while the remaining 34.6% is influenced by other variables. The results of this study can contribute to an understanding of the factors that influence the village community's interest in becoming customers in Islamic banks